LOCALIZATION AND SECRETION OF SALT BY THE SALT GLANDS OF Tamarix aphylla - Thomson, W. W. (1969)
Analysis of salt secreted by the salt glands of Tamarix aphylla shows that the composition of the secreted salt is dependent on the salt composition of the root environment. Rubidium ion, if added to culture solutions in which the plants were growing, is also taken up by the plants and subsequently secreted by the glands. Electron micrographs of glands from the ribidium-secreting plants show accumulations of electron-dense material in the microvacuoles of the secretory cells. It is concluded that rubidium is accumulated in the microvacuoles and subsequently secreted by their fusion with the plasmalemma.